Streaming Potential Coupling Coefficient and Transport Properties of Unsaturated Carbonate Rocks. Issue 1 (4th October 2018) - Cherubini, A.; Garcia, B.; Cerepi, A.; Revil, A.
Abstract : Core Ideas: Streaming potential coupling coefficient is dependent on saturation in carbonate rocks. Salinity influences the streaming potential coupling coefficient. Water relative permeability can be estimated from streaming potential measurements. Transport properties of carbonate rocks can be modeled using the van Genuchten approach. We measured the streaming potential coupling coefficient of natural saturated and unsaturated carbonate rocks. Saturation was achieved with NaCl brines with salinities ranging from 2 × 10 −3 to 2.0 mol L −1 . The magnitude of the coupling coefficient increased with decreasing salinity, similarly to the trend observed for sandstones. The permeability had a low impact on the values of the streaming potential coupling coefficient at high and low salinity. The zeta potential was calculated at full saturation using a modified version of the Helmholtz–Smoluchowski equation that accounts for surface electrical conductivity. Under atmospheric conditions, the magnitude of the zeta potential decreased with the increase in salinity. We also explored the relationships between the streaming potential coupling coefficient and water saturation in three partially saturated limestones using a steady‐state flow experiment. We found good agreement between the van Genuchten approach and experimental data, and fitted both the relative permeability and capillary pressure curves with the same value of the van Genuchten exponent m v . We validated the predictive water relative permeability model described by Revil in water‐wet rocks when the second fluid phase is non‐polar.